2020
DOI: 10.1017/cjn.2020.126
|View full text |Cite
|
Sign up to set email alerts
|

Variants inCHRNB2andCHRNA4Identified in Patients with Insular Epilepsy

Abstract: Purpose: Our purpose was to determine the role of CHRNA4 and CHRNB2 in insular epilepsy. Method: We identified two patients with drug-resistant predominantly sleep-related hypermotor seizures, one harboring a heterozygous missense variant (c.77C>T; p. Thr26Met) in the CHRNB2 gene and the other a heterozygous missense variant (c.1079G>A; p. Arg360Gln) in the CHRNA4 gene. The patients underwent electrophysiological and neuroimaging studies, and we performed functional characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The expression and prognosis of TUBB2A [399], PAK1 [400], PRKCG (protein kinase C gamma) [401], CACNA1G [402], ATP1A3 [403] and KCNJ10 [404] have been investigated in ataxia. SCN3B [405], PCDH19 [406], CNTNAP2 [407], STXBP1 [408], CHRNB2 [409], NAPA (NSF attachment protein alpha) [410], STX1B [411], GABRG2 [412], CAMKK2 [144], CNTNAP2 [413], ARHGEF9 [414], COX8A [415], CALHM1 [416], SLC45A1 [417], TLR5 [418] and KCNJ10 [419] could be acuseful prognostic biomarker in epilepsy. The altered expression of NPTX2 [420], VAMP2 [421], PRKAR1B [422], SNCB (synuclein beta) [199], AP2M1 [423], TUBA4A [424], KIF17 [425] and SYK (spleen associated tyrosine kinase) [426] might be related to the progression of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and prognosis of TUBB2A [399], PAK1 [400], PRKCG (protein kinase C gamma) [401], CACNA1G [402], ATP1A3 [403] and KCNJ10 [404] have been investigated in ataxia. SCN3B [405], PCDH19 [406], CNTNAP2 [407], STXBP1 [408], CHRNB2 [409], NAPA (NSF attachment protein alpha) [410], STX1B [411], GABRG2 [412], CAMKK2 [144], CNTNAP2 [413], ARHGEF9 [414], COX8A [415], CALHM1 [416], SLC45A1 [417], TLR5 [418] and KCNJ10 [419] could be acuseful prognostic biomarker in epilepsy. The altered expression of NPTX2 [420], VAMP2 [421], PRKAR1B [422], SNCB (synuclein beta) [199], AP2M1 [423], TUBA4A [424], KIF17 [425] and SYK (spleen associated tyrosine kinase) [426] might be related to the progression of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an increase of midbrain nAChRs density could be involved in the pathological of ADSHE through the brainstem cholinergic signaling in the ascending arousal system [ 56 ]. A study of ADSHE variants in CHRNB2 and CHRNA4 closely relevant to patients with insular epilepsy recently, CHRNB2 and CHRNA4 increased nicotinic currents in whole-cell recording [ 57 ]. In addition, clinical data demonstrated that mutations in CHRNA4 may be a novel gene causing genetic or focal epilepsy with febrile seizures [ 58 ] and familial partial epilepsy with variable foci [ 59 ], it aims to broaden the genotypic-phenotypic spectrum of combined epileptic in CHRNA4 .…”
Section: Cholinergic Signaling In Epilepsymentioning
confidence: 99%
“…[56] Patients with insular epilepsy Interictal period Mutant nACh receptors increased nicotinic currents in whole-cell recording. [57] Genetic or focal epilepsy with febrile seizures (GEFS+) patients…”
Section: Adshe Patientsmentioning
confidence: 99%
“…ADSHE-linked mutations were soon also found on CHRNB2 [46,47], and the number of ADSHE mutations found on CHRNA4 or CHRNB2 has subsequently increased at a steady pace [19,48,49]. Recently, variants of heteromeric nAChR subunits have been also suggested to be implicated in other epileptic forms [50][51][52]. In contrast, despite the wide expression of α7 receptors in the brain [30], evidence about the involvement of CHRNA7 in epilepsy is weak.…”
Section: The α4 and β2 Nachr Subunits In Adshementioning
confidence: 99%